2021
DOI: 10.2147/cmar.s332612
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lymph Node Characteristics in Patients with Cervical Cancer Treated with Radical Hysterectomy

Abstract: Objective: This study evaluated the prognostic value of various lymph node (LN) characteristics, including the lymph node ratio (LNR), in patients with cervical cancer treated with radical hysterectomy. Methods: In this retrospective study, 260 patients with cervical cancer who had undergone radical hysterectomy with pelvic or paraaortic lymphadenectomies were included. LN characteristics related to several LN statuses included total LN counts, LN metastasis, total positive LN counts, LNR, and levels of lympha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We chose LNR to represent the LN status in this study due to the most excellent prediction ability of this index compared with other LN indices. 18,22,24 The LNR, covering the information on the number of positive LNs and retrieved LNs (RLNs), was genetically insufficient to differentiate the survival for patients with different positive LNs and RLNs but shared the identical LNR, it is, whether patients with 1 positive LN of 1 retrieved LN performed equally in survival when compared with the patients with 10 positive LNs of 10 retrieved LNs. Owing to this fact, only patients receiving adequate lymphadenectomy (the number of RLNs during the surgery exceeded 8) were included in our study to partially alleviate the effect of the limitation of LNR on the survival prediction, which might further increase the generalizability and universality of this risk scoring system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose LNR to represent the LN status in this study due to the most excellent prediction ability of this index compared with other LN indices. 18,22,24 The LNR, covering the information on the number of positive LNs and retrieved LNs (RLNs), was genetically insufficient to differentiate the survival for patients with different positive LNs and RLNs but shared the identical LNR, it is, whether patients with 1 positive LN of 1 retrieved LN performed equally in survival when compared with the patients with 10 positive LNs of 10 retrieved LNs. Owing to this fact, only patients receiving adequate lymphadenectomy (the number of RLNs during the surgery exceeded 8) were included in our study to partially alleviate the effect of the limitation of LNR on the survival prediction, which might further increase the generalizability and universality of this risk scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…A few of the previous studies have explored the prognostic significance of the LNR in cervical cancer patients with LN metastases,18–20,22,23 seldom of which has further investigated the role of LNR in aiding in the adjuvant treatment decision making. We chose LNR to represent the LN status in this study due to the most excellent prediction ability of this index compared with other LN indices 18,22,24. The LNR, covering the information on the number of positive LNs and retrieved LNs (RLNs), was genetically insufficient to differentiate the survival for patients with different positive LNs and RLNs but shared the identical LNR, it is, whether patients with 1 positive LN of 1 retrieved LN performed equally in survival when compared with the patients with 10 positive LNs of 10 retrieved LNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biglia et al found that neither chemotherapy alone nor the association of consecutive chemotherapy and radiotherapy was associated with an increased incidence of lower limb lymphedema ( 13 ). In addition, there have been a few studies investigating the risk factors including BMI, nutritional status, number of removed lymph nodes, lymphedema, and adjuvant radiotherapy in patients having systematic lymphadenectomy ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognosis of stage III and IV patients remains poor, with 5-year progression-free survival (PFS) and overall survival (OS) rates of 51% and 55%, respectively ( 20 ). Pelvic lymph node metastasis remains an important independent prognostic factor for CC In addition, it is associated with a lower 5-year survival rate and a higher recurrence rate ( 21 23 ). However, there is no effective method to control and prevent lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%